1992
DOI: 10.1016/0014-5793(92)81468-2
|View full text |Cite
|
Sign up to set email alerts
|

‘All‐or‐none’ mechanism of the molten globule unfolding

Abstract: The Gdm-HCl-induced unfolding of bovine carbonic anhydrase B and S. at~ret~s fl-lactamase was studied at 4°C by a variety of methods. With the use of FPLC it has been shown that within the transition from the molten globule to the unfolded state the distribution function of molecular dimensions is bimodal. This means that equilibrium intermediates between the molten globule and the unfolded states are about, i.¢. the molten globule unfolding follows the "all-or-none' mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
59
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 21 publications
2
59
0
Order By: Relevance
“…It has also been used to obtain the hydrodynamic data of the intermediates, as well as to observe changes in the molecular dimension in N4I and I4U transitions (37,38). In the case presented here, the study of urea-induced unfolding of CPR3 by SEC suggested the existence of two intermediates in the unfolding pathway.…”
Section: Ans Fluorescence Studymentioning
confidence: 85%
See 1 more Smart Citation
“…It has also been used to obtain the hydrodynamic data of the intermediates, as well as to observe changes in the molecular dimension in N4I and I4U transitions (37,38). In the case presented here, the study of urea-induced unfolding of CPR3 by SEC suggested the existence of two intermediates in the unfolding pathway.…”
Section: Ans Fluorescence Studymentioning
confidence: 85%
“…Urea-induced unfolding of CPR3 studied by SEC SEC is a wonderful technique for identifying intermediates in the unfolding process (37,38). It has also been used to obtain the hydrodynamic data of the intermediates, as well as to observe changes in the molecular dimension in N4I and I4U transitions (37,38).…”
Section: Ans Fluorescence Studymentioning
confidence: 99%
“…4). Multiphasic equilibrium unfolding profiles, monitored by FPLC, have been reported in several proteins and are attributed to the formation of intermediates in the time scales of the FPLC experiments (27,28). The first phase of unfolding (0 -1.0 M GdnHCl) of hFGF-1 appears to represent an equilibrium transition between the native and the intermediate state(s).…”
Section: Gdnhcl-induced Unfolding Of Hfgf-1 Is Not a Two-statementioning
confidence: 95%
“…Unfolding of hFGF-1 Occurs in Two Stages-Size exclusion chromatography (SEC) is an useful technique to obtain information of integral changes of molecule dimensions under denaturant effect (27,28). This technique has been successfully used to identify and obtain hydrodynamic data on stable intermediates in the folding/unfolding pathway(s) of proteins (27).…”
Section: Gdnhcl-induced Unfolding Of Hfgf-1 Is Not a Two-statementioning
confidence: 99%
“…It differs from the native state mainly by the absence of tight packing of side chains and by a substantial increase of their fluctuability. It has been recognized that the molten globule can be considered as the third thermodynamic state of protein molecule in addition to the native and completely unfolded states (Uversky et al, 1992; Ptitsyn & Uversky, 1994; Uversky & Ptitsyn, 1996). The physiological importance of the molten globule state has been suggested and confirmed experimentally (see Bychkova & Ptitsyn, 1993, for review).…”
mentioning
confidence: 99%